CHEMICAL COMPOSITION OF ESSENTIAL OILS EXTRACTED FROM Melaleuca citrina (Curtis) Dum. Cours. LEAVES (Applied Biological Research, 2024)
The medicinal properties of plants have been known for centuries, making  them an invaluable resource for the people in need of treatment. Humans on  every continent have long relied on the healing properties of plants, a  practice that may be traced back to prehistoric times. Melaleuca citrina is a  plant with substantial therapeutic potential. To the best of our knowledge, no  published work has characterized the chemical composition of M. citrina in  Nigeria. This study aimed to analyse the bioactive chemical constituents of  essential oil extracted from the leaves of M. citrina in Nigeria. A Clevenger style apparatus was used to hydro-distillate the freshly chopped leaves of M.  citrina for a duration of two to three hours. After the extraction process, the  essential oils were separated and dried using anhydrous sodium sulphate.  Then, the oil composition was examined using gas chromatography-mass  spectrometry. Here are the main compounds: (-) Spothulenol 8.6%,  Cryptomeridiol 5.5%, Selinene gamma 8%, Pinocarveol cis-> 15%, Cymene  para 10%, Selinene delta 10%, and globulol 27.3%. Astringent, antibacterial,  anti-inflammatory, and antiseptic are just a few of the fascinating biological  characteristics exhibited by globulol, the main component of essential oils.  Essential oils extracted from the leaves of Melaleuca citrina possess strong  natural qualities that can work as anti-inflammatory, antibacterial,  antiseptic, and astringent agents.
Keywords: Aromatic; antimicrobial; essential oil; Nigeria